Correlation between the Arm weapon and the First touch with achievement on Wheelchair Fencing - Hamid, Abedulhadi (Journal of Physical Education, 2007)
This event requires endurance, speed, force and other features of physical body like the Anthropometry. The problem of this research to know the effect of long arm weapon in achievement also the effect of the first touch and the correlation with achievement . This search application on the Epee players (25A+ 16B)participate on the World cup Wheelchair Fencing -2005 in Italia . The researcher reaches to some Conclusion that is lick: We find there is no static’s correlation between the arm weapon with achieving for Epee players (A+B) but we found there is appositive correlation between the arm weapon from Epee players (A) , they played 84 match ( the match end for the player who register the first touch 55 match represent 65.48%.but the loser 29 match represent 34.52%),players (B) played 69 match ,the winner 50 match represent 72.46%and the loser 19 match represent 27,54%. The all match for all players (A+B) they played 153 match , the winner (105 match)represent 68.63% and the loser ( 48 match) represent 31.37% The researcher reaches to some recommendation that is lick: • Must put special time for physiological preparing in unit training. • put program training to developing the level of act planning for attack skills . •